Hubungan Antara Titik Panas Dan Nesting Ground Burung Maleo (Macrocephalon maleo) Di Desa Kadidia Kecamatan Nokilalaki Kawasan Taman Nasional Lore Lindu - Mallombasang, Sri Ningsih (ForestSains, 2019)
Study conducted for two months tking place at Kadidia Village, Lore Lindu National Park.  Data analysis used was qualitative descriptive by interpreting the site under study.  It was conducted by recording the number heat points of a nesting ground, distance between the nesting grounds, active and pseudo nesting ground and the number of eggs found.  Observation was focused on three spots.  The relation between the number of heat poits and the nesting ground was tabulated and treated as the initial information.  Community members who occasionally collect the eggs were interviewed.  The result of the study found that from three spots studied, Spot 1 containing 6 heat points with the number of nesting ground of 195, Spot 2 with 5 heat points and 83 nesting grounds and Spot 3 with 4 heat points and 79 nestng grounds all with heat points dispersed contagiously.  The threats for the eggs are coming from lizards and human and flooding in rainy season.